“Factors Associated with Perceived Change in Weight, Physical Activity, and Food Consumption during the COVID-19 Lockdown in Latin America“ - Mejia, Christian R. (2023)
“Quarantine and the restrictions necessitated by the COVID-19 pandemic have generated problems in nutrition and physical condition around the world. We aimed to determine factors associated with changes in perceived weight and lifestyle factors during the COVID-19 quarantine in Latin America, conducting a cross-sectional study based on a survey administered in more than a dozen countries during June–August 2020. Perceptions of weight changes and alterations in other habits were investigated and were associated with social factors and self-reported diseases. Of 8800 respondents, the majority perceived that they had gained weight and had been less physically active. Being female, living in Bolivia, obesity, and stress were factors associated with a higher perception of weight gain. A higher perception of physical activity was also associated with living in Chile, being of older age, being female, having diabetes, obesity, and stress. When living in Paraguay and Mexico, being female, obesity, anxiety, and stress were associated with a higher perception of unhealthy food consumption. When living in Bolivia, women, obesity, and stress were associated with a higher perception of consuming larger food portions. In conclusion, the perceived changes in weight and lifestyle during the pandemic were more evident in women, people with comorbidities, and those with emotional distress. Differences in the perception of weight changes were minimal among Latin American countries. This information suggests the possible metabolic implications in at-risk individuals that should be further addressed by researchers for timely intervention. “